Vivência de uma época desportiva numa equipa profissional de futebol. Reflexão sobre o processo de treino, tendo como base a forma de jogar idealizada pelo treinador - Miguel Fernando Pinto Santos (2016)
In the last two decades it has been visible a significant evolution in football, not only with regard to game and the sports spectacle that competition provides, but also the way it conceives, constructs and intervenes in the training process. The training process is a phenomenon that involves a highly complex because it includes multiple factors that need to be converged. So, and for that this convergence becomes as effective as possible, the coaches create own models with the goal of guide the whole process for something they want to achieve. In football, coaches have as one of the great purposes of your training process to implement their style of play idealized, presenting as main models in their process: the game model, the training model and the observation and analysis model. This study had as main goal understand how it's prepared and done all the training process, based on the game model and training model conceptualized and operationalized by the coach. For this, it was done in the 2nd cycle in High Performance Sports at FADEUP, a stage of a sports season in a professional team of the 1st Portuguese League, FC Paços de Ferreira. Through the experience obtained, the information gathered from the literature review, and personal reflections, it was possible conclude: (1) the conception of a game model is a fundamental aspect of the process, because it's from this that everything is conceived; (2) it's essential to create and operationalize a specifictraining model because it will allow to implement the ideas conceived game model; (3) the existence of an observation and analysis model is a determining factor in the assessment and control of the process developed; (4) finally, for the process to be as effective as possible is crucial to establish a congruence between all the conceptualized models.